Effect of sodium bisulfate and in-feed antimicrobial products on Salmonella Enteritidis survival and nutrient digestibility in contaminated broiler breeder diets - M.K. Jones; J.A. Baxter; C.L. Hofacre; R.D. Berghaus; J.C. Suarez; C.D. Coufal; J.C. Jespersen; A.J. Davis (Journal of Applied Poultry Research)
Summary: Antimicrobial products such as formaldehyde and formic acid can reduce pathogen levels in finished feed or the gastrointestinal tract. Some feed mill interventions decrease bacteria, but the degree of reduction, impact on digestibility, and interaction between other ingredients is unknown. We assessed two antimicrobial products with and without sodium bisulfate (SBS) as the primary sodium source in broiler breeder diets for efficacy against Salmonella Enteritidis (SE) load and impact on nutrient digestibility. Treatments included 1) a sodium bicarbonate (SBC) control diet, 2) SBC diet plus formaldehyde-based product (3 kg/MT), 3) SBC diet plus formic acid-based product (3 kg/MT), 4) SBS control diet (4 kg/MT), 5) SBS diet plus formaldehyde-based product (3 kg/MT), and 6) SBS diet plus formic acid-based product (3 kg/MT). Feed was contaminated with SE using meat and bone meal to achieve ∼106 cfu/g, and SE was enumerated at 0, 1, 2, and 7 d post-contamination. Uncontaminated diet samples were fed to Leghorn roosters and excreta samples were collected for nutrient analysis. SBS diets with the formaldehyde-based product had lower SE counts on d 0 compared to SBS control. This pattern continued with reduction in SE in both formaldehyde groups relative to other treatments, and by d 7 the Salmonella outcomes were zero in formaldehyde-treatments. TMEn was not different between treatments. Arginine and proline had lower digestibility coefficients in SBS diets with formic acid relative to SBS control. The tryptophan digestibility coefficient was higher in the SBS control diet relative to the SBC control. Collectively, these results indicate the primary sodium source had no negative impact on efficacy of Salmonella reduction in feed, however, an interaction may exist between formic acid and amino acid digestibility.